Antimony Sulfoiodide-Based Energy Harvesting and Self-Powered Temperature Detection - Song, Heewon; Hajra, Sugato; Panda, Swati; Hwang, Subhin; Kim, Nayoon; Jo, Junghun; Vittayakorn, Naratip; Mistewicz, Krystian; Joon Kim, Hoe (My University, 2024)
The ferroelectric-semiconductor behavior of antimony sulfoiodide (SbSI) has opened up the material as a base for energy-harvesting devices. Specifically, SbSI has drawn much attention for pyroelectric energy harvesting and thermal sensing with outstanding electrothermal properties. This work investigates the thermistor properties of an SbSI material and presents the development of an SbSI nanorod/Kapton-based triboelectric nanogenerator (TENG) for effective energy harvesting and temperature sensing. The TENG based on SbSI/ Kapton operating in vertical contact separation mode delivers a peak-to-peak voltage of 90 V and a current of 1510 nA, respectively. Introducing SbSI nanorods for TENG opens the possibility of extending the conventional triboelectric series. The electrical and dielectric properties of the SbSI nanorods are investigated. SbSI exhibits a highly linear temperature coefficient of resistance (TCR) of −0.026 °C−1, making it an excellent candidate material for a thermistor. In addition, the material exhibits an excellent thermal sensitivity (β20/80 = 1612.1 K). For demonstration, the SbSI thermistor is connected with TENG, and the outputs at various temperatures are analyzed for self-powered temperature sensing. This capability allows for efficient temperature monitoring without relying on external power sources, advancing remote, and autonomous sensing applications.
Keywords: dielectric; nanorods; temperature; triboelectric